IMPLEMENTASI PENGUKURANCONDUCT DISORDER UNTUK MEMBANTU PSIKIATER PADA ANAK - Sigit Birowo (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Technological developments that so quickly affect various aspects of life. One of them is aninformation system. Where these developments have a very large influence on individuals orpeople in information or information. Evolution helps in various fields of life, one of which ishealth psychology.In this study, the authors use theory of data, systems, and information systems. Besides thatthe author also uses web theory, understanding and conduct conduct criteria.Information gathering is done by structured interviews, namely by conducting interviews withDr. Myra, M.Kes, SP.KJ, also indirectly and also literature study.This calculation system is made to determine symptoms of disorders in children based onMAS (Motivation Assessment Scale) and can be used to help psychiatrists, in diagnosing thecauses of behavioral disorders.Through the research process that has been carried out and the application developmentprocess that has been carried out, researchers conclude that the application that researchers can helpdetermine behavioral disorders in children and help in disseminating behavioral disorders.Key words: Psychiatrists, Conduct Disorder , Children, MAS(Motivation Assesment Scale).